BENTUK, FUNGSI DAN MAKNA: AFIKSASI PADA LIRIK LAGU CAMPURSARI DIDI KEMPOT - Fuji Savitri Fuji Savitri; Fitri Fitri; Sri Mulyani (Penerbit Lafadz Jaya, 2023)
The background of this research is the campursari song which is still considered classic and out of date with existing music. The name campursari is taken from the Javanese language which is actually general in nature. Campursari comes from a combination of keroncong and traditional Javanese music or karawitan (keroncong and traditional Javanese music/gamelan). Based on this description, the formulation of the problem in this study is how the form, function, meaning of affixes, and implementation of the Indonesian language learning implementation plan. This research method is a descriptive method with a qualitative research form. The analysis technique uses descriptive techniques. Check the validity of the observation persistence data, triangulation, and adequacy of references. The results of the analysis of form, function and meaning: affixation to the lyrics of the Didi Kempot Campursari song can be concluded: (1) there are 4 types of affix forms. (2) The function of the affix in the lyrics of the Didi Kempot campursari song is that there is a prefix meng- that functions to form an intransitive verb. (3) The meaning of the affixes in the lyrics of the Didi Kempot campursari song is that there is a prefix meng- meaning 'process', 'become'. The results of the analysis were obtained from the lyrics of the Didi Kempot campursari song which was contained in two VCD cassettes. (4) Implementation in the form of a Learning Implementation Plan, which will be used in the learning process in class X high school level with basic competency 3.4 namely explaining morphological processes (affixation, compounding, repetition, and absorption) in sentences.